2012
DOI: 10.1002/pro.2117
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of designed armadillo repeat proteins by molecular dynamics simulations and NMR spectroscopy

Abstract: A multidisciplinary approach based on molecular dynamics (MD) simulations using homology models, NMR spectroscopy, and a variety of biophysical techniques was used to efficiently improve the thermodynamic stability of armadillo repeat proteins (ArmRPs). ArmRPs can form the basis of modular peptide recognition and the ArmRP version on which synthetic libraries are based must be as stable as possible. The 42-residue internal Arm repeats had been designed previously using a sequence-consensus method. Heteronuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…Figure S8). Therefore, the Rosetta model of CAR0 was used as starting structure for multiple explicit solvent MD runs (of 0.5 to 2 µs each) to identify regions with high flexibility and stabilize them, as described before [9]. The MD trajectories showed that the overall fold of model CAR0 was preserved, with an average root mean square fluctuation (RMSF) of 0.4 Å for the C α carbon atoms (the RMSD is given in Supplementary Table ST2).…”
Section: Experimental Validation Of Computationally Designed Armrpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure S8). Therefore, the Rosetta model of CAR0 was used as starting structure for multiple explicit solvent MD runs (of 0.5 to 2 µs each) to identify regions with high flexibility and stabilize them, as described before [9]. The MD trajectories showed that the overall fold of model CAR0 was preserved, with an average root mean square fluctuation (RMSF) of 0.4 Å for the C α carbon atoms (the RMSD is given in Supplementary Table ST2).…”
Section: Experimental Validation Of Computationally Designed Armrpsmentioning
confidence: 99%
“…for DARPins [22] and consensus-based ArmRPs [9,10]. For dArmRPs, the impact of the Y III -capping repeat was additionally tested on the original, computationally designed protein These results do not allow us to decide whether the capping repeat has an influence on the overall curvature or not.…”
Section: Stabilization Effect Of the Y III -Capping Repeat With The Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple copies of the unit are then linked to create a homogeneous repeat protein sequence; capping repeats are derived from naturally existing proteins. Consensus design has been the first and most widely used approach across multiple repeat protein families: ankyrin (ANK) [9][10][11][12][13], tetratricopeptide repeat (TPR) [14], armadillo (ARM) [15][16][17], leucine rich repeat (LRR) [18], pentatricopeptide repeat (PPR) [19,20], pentapeptide repeat [21], 42 residue TPR variant (42PR) [22] and HEAT-EZ [23], all have designed structures confirmed by crystallography (Table 1). Effective consensus design relies on the assumption that evolutionary conservation translates into self-compatibility of repeats and foldability of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Further restricting the MSA to narrow and homogeneous groups within the families produced successful designs in some cases [18,23]. Using structure information and molecular dynamic simulations produced stable ARM designs; ARM designs from consensus were molten globule-like [15,16]. Instead of extracting a consensus sequence, Lee and Blaber [25,26] progressively introduced mutations experimentally to a beta trefoil background to arrive at sequences that contain three identical tandem repeats.…”
Section: Introductionmentioning
confidence: 99%